Endangered Saudi Arabian plants having ethnobotanical evidence as antidotes for scorpion envenoming - Abdulrahman Khazim Al-Asmari; Rajamohamed Abbasmanthiri; Nasreddien Mohammed Abdo Osman; Byan Abdulrahman Al-Asmari (Clinical Phytoscience, 2020)
Abstract Scorpion sting envenoming in Saudi Arabia posed major public health problems. Conventional treatment with antivenom with its limitations and hazards called for the use of support remediation like prazosin therapy and phytotherapy as alternative solutions in systematic medicine and a trend of use in medicinal plants. The present study is aiming to procure the medicinal plants that exhibit antidotes of scorpion stings which, were scientifically ignored in Saudi Arabia. Current study data of 11 rare and endangered medicinal plants were collected identified up to the family level, in addition to the parts used. The Family Leguminosae was represented by 4 species. The families Acanthaceae, Amaranthaceae, Annonaceae, Euphorbiaceae, Myrtaceae, Plumbaginaceae, and Zygophyllaceae, were represented with a single species each. All of them have got medicinal ability of antidote potential against scorpion venoms. These commonly used herbs that belonged to 8 families were similar in the use of all parts in treatment. This review study may assist the researchers recruiting new natural herbs and their active products as therapeutic agents against scorpion envenoming. However, these medicinal plants are still requiring pharmacological and phytochemical investigations in order to be claimed as effective antidotes in scorpion envenoming syndrome.